A Study to Assess the Knowledge and Compliance of Critical Care Nurses Regarding Ventilator Care Bundle in Prevention of Ventilator Associated Pneumonia (Medico Legal Update, 2019)
Mechanical ventilation is one of the major supportive modalities in the intensive care unit but it carries a lot of risks and complications, the most common one being VAP. VAP is a problem in intensive care units worldwide and dramatically increases morbidity and mortality rates on mechanically ventilated patients. It is the most common infectious complication among patients admitted to intensive care unit[1]. Knowledge of nurses on ventilator care bundle for the prevention of VAP and adherence to them would reduce the risk of occurrence of VAP and decrease morbidity and mortality of mechanically ventilated patients in the ICU. Nursing care is growing rapidly in conjunction with technology and it is catching up with developed countries guidelines and standards of care. Nursing shortage, however, is a burden and intensive care nurses are in huge demand .The few intensive care nurses still practicing need to constantly update themselves with current knowledge and scientific evidence on many issues existent in the ICU,including VAP [2]. The four primary recommended practices includes: elevating the head of the bed to 30 degrees, sedation vacations, oral care with chlorohexidine (CHG) and subglottic suctioning endotracheal tubes. Ventilator “bundles” usually include other elements such as deep venous thrombosis (DVT) prophylaxis, peptic ulcer prophylaxis. The nurse are expected to care for these patients in a setting of intensive care unit. The nurses should have thorough knowledge of the modes of ventilation, assessment, and trouble shooting of ventilators and assessment and care of the patients requiring mechanical ventilation.[3,4]The result shows that more than half (56.7%) of the staff nurses had excellent knowledge regarding ventilator care bundle and 43.3% of them had good knowledge regarding ventilator care bundle It shows that knowledge and compliance of staff nurses regarding ventilator care bundle were found to have significant association.